Environmental Fiqh and Protecting Nature: How Islamized View on Nature Implemented - Bahrum Subagiya (Universitas Darussalam Gontor, 2025)
An important cause of the destruction of nature begins with a materialistic human worldview. Nature and the environment are only seen as objects to fulfill human life. Thus, nature is overused, in order to satisfy lust without looking at its sustainability in a sustainable future. This study examines several fatwas of the Indonesian Ulema Council (MUI) related to the environment. With a library research approach, researchers found that the MUI fatwa has an important role in changing the way humans view nature and the environment. The nature of nature is not only a physical essence that is materialistic, but nature is an important part of human life that has spiritual values. Nature is entrusted by Allah, not the property of humans, but Allah gives wide authority in its management. Therefore, nature management cannot be separated from the guidelines of the Shari'ah, in this case what is already contained in the Qur'an and Hadith.